Effect of adhesive concentration and particle size on the quality of hazelnut shell briquettes with glutinous rice adhesive - Huda, Ahmad Akromul; Karyanik, Karyanik; Muliatiningsih, Muliatiningsih; Fathoni, Ahmad; Hakim, Abdul (Universitas Muhammadiyah Mataram, 2023)
One alternative energy that can be used as a substitute for fuel oil and gas is biomass energy such as briquettes. This study aims to determine the amount of heat, moisture content and ash content of briquettes made using hazelnut shells and glutinous rice adhesives that vary in adhesive concentration and particle size. This study used a complete randomised design (CRD) with variations in glutinous rice concentration of 20%, 30%, and 40% while the particle sizes used were 12 mesh and 24 mesh. The results showed that the adhesive concentration did not significantly affect the test parameters while the particle size affected the moisture content, ash content and calorific value of the briquettes. The highest calorific value was obtained by using 24 mesh particle size with 20% adhesive concentration with a calorific value of 5321 cal/g while the 12 mesh particle size produced the highest calorific value of 4704 cal/g at 20% adhesive concentration. The lowest moisture content value was obtained by using 24 mesh particle size with 20% adhesive concentration with a moisture content value of 6.9% while the 12 mesh particle size produced the lowest moisture content value at 20% adhesive concentration with a value of 7.4%. The lowest ash content value was obtained by using 24 mesh particle size with 30% adhesive concentration with an ash content value of 4.99% while the 12 mesh particle size produced an ash content value of 5.82%. The use of 12 mesh particle size is not in accordance with SNI standards because the heating value produced is still below 5000 cal/gr while the use of 24 mesh particle size is in accordance with SNI standards for all test parameters.